Characteristics of human thermal stress in South Asia during 1981–2019. (23rd September 2022) - Ullah, Safi; You, Qinglong; Wang, Guojie; Ullah, Waheed; Sachindra, D A; Yan, Yechao; Bhatti, Asher Samuel; Abbas, Adnan; Jan, Mushtaq Ahmad
Abstract: Climate change has significantly increased the frequency and intensity of human thermal stress, with relatively more severe impacts than those of pure temperature extremes. Despite its major threats to public health, limited studies have assessed spatiotemporal changes in human thermal stress in densely populated regions, like South Asia (SAS). The present study assessed spatiotemporal changes in human thermal stress characteristics in SAS, based on daily minimum, maximum, and mean Universal Thermal Climate Indices (i.e. UTCImin, UTCImax, and UTCImean ) using the newly developed high-spatial-resolution database of the thermal-stress Indices over South and East Asia for the period 1981–2019. This study is the first of its kind to assess spatiotemporal changes in UTCI indices over the whole of SAS. The study also carried out extreme events analysis of the UTCI indices and explored their nexus with El Niño-Southern Oscillation (ENSO) index. Results revealed a significant increase in heat stress in SAS, with the highest human thermal stress in western Afghanistan, the Indo-Gangetic Plain, and southeastern, and central parts. The extreme event analysis showed that the study region is likely to observe more frequent and intense heat extremes in the coming decades. The correlation of UTCI indices with ENSO exhibited a robust positive coherence in southeastern and central India, southern Pakistan, and northwestern Afghanistan. The findings of the study are critical in understanding human thermal stress and adopting effective risk reduction strategies against heat extremes in SAS. To better understand the dynamic mechanism of thermal extremes, the study recommends a detailed investigation of the underlying drivers of UTCI variability in SAS.